The Effect of Culture Techniques of Hypoxic Stem Cell Secretome on The Number of Growth Factor TGF-β, BMP-2, VEGF - Edward, Mouli; Mahyudin, Ferdiansyah; Manyakori, Dionysius Bramta Putra (Universitas Airlangga, 2022)
Background: Mesenchymal stem/stromal cell (MSC) therapy is now an effective therapeutic modality for treating various diseases. In its application, stem cells require signaling molecules, including growth factors, cytokines, and chemokines. Signaling molecules function in an orderly manner and are greatly influenced by the physiological environment. Stem cell culture techniques with hypoxic conditions can produce growth factors similar to those found in fracture conditions. This study aimed to evaluate the differential expression of growth factors in cultured normoxic and hypoxic bone marrow stem cell (BMSCs).Methods: This in vitro laboratory experimental study examined normoxic and hypoxic BMSC cultures. BMSCs were harvested from rabbits, propagated in vitro, and cultured under normoxic and hypoxic conditions. Vascular endothelial growth factor (VEGF), Transforming growth factor-β (TGF-β), and Bone morphogenetic protein-2(BMP-2) levels were measured using ELISA.Results: VEGF, TGF-β, and BMP-2 expression showed significant differences between the normoxia and hypoxia groups. The VEGF, TGF-β, and BMP-2 expressions were higher in the hypoxia group compared with the normoxia group (p < 0.05).Conclusion: The expression of TGF-β1, VEGF, and BMP-2 growth factors in cultured BMSCs was significantly different between normoxic and hypoxic conditions. TGF-β1, VEGF, and BMP-2 expression increased under hypoxic conditions.